POLA MANAJEMEN PONDOK PESANTREN AL-RAISIYAH MATARAM - Yakin, Nurul (JURNAL PENELITIAN KEISLAMAN, 2013)
This study aims to discuss in detail about: (1) the management pattern of curriculum used, (2) the management pattern of teacher and educational staff, (3) the management pattern of budgetary fund of Pondok Pesantren Al-Raisiyah in Mataram. The methodology used in this study was qualitative with a case study intrinsic design. The data were collected by using interviews, participative observations and documentations. The data collected were examined its truth, congeniality and reliability through triangulation method and source. Furthermore, they were organized, analyzed and inferred in each case of study, and were compared with the data of other studies, then the conclusion was gained.As a result, the study found that (1) the curriculum used at Pondok Pesantren Al Raisyiah consisted of two models, namely School-Based Curriculum (Kurikulum Tingkat Satuan Pendidikan/KTSP) and âTakhassus Curriculumâ Particular/typical curriculum. The particular/typical curriculum emphasized on studying classical/old Islamic books especially Arabic Grammar which was familiarly known as Nahwu by the students and the villagers. (2) The management pattern of teacher and educational staff prioritized on pointing the relatives of Pondok Pesantren and the aboriginal inhabitants of Sekarbela. The other persons who were not from both criteria were also possibly recruited if they could fulfill requirements proposed. (3) The management pattern of budgetary fund implemented an open management which stressed on values of honesty and sincerity in all of the implementation.